Penggunaan Media Visual dalam Proses Pembelajaran - Budiman, Haris (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Conventional teaching and learning process it has many shortcomings, which are caused by not all teachers have the same competence, differences in absorption of learners in listening to lessons, teaching materials that teachers have limited and learning activities for students as objects tend to be boring.               For that teachers are required to have creativity in teaching, teachers are required able to stimulate learners to be proactive in learning activities. Like a bridge connecting the two sides, the role played by media learning in a teaching system. That role becomes vital for visual learning media is not only responsible for the arrival of a message to student learning, but also ensures that the message does not degrade or irregularities meaning. Thus a learning process by using visual media can boost creativity and motivation for learners to learn and can be done effectively and efficiently.